Comparative pathogenicity of CA1737/04 and Mass infectious bronchitis virus genotypes in laying chickens - Ali, Ahmed; Farooq, Muhammad; Altakrouni, Danah; Najimudeen, Shahnas M.; Hassan, Mohamed S. H.; Isham, Ishara M.; Shalaby, Adel A.; Gallardo, Rodrigo A.; Abdul-Careem, Mohamed Faizal (Frontiers in Veterinary Science, 2024)
Infectious bronchitis virus (IBV) is a respiratory virus with atropism to multiple body systems of chickens. Recently, California 1737/04 (CA1737/04) IBV strain was identified as one of the circulating IBV variants among poultry operations in North America. Here, the pathogenicity and tissue tropism of CA1737/04 IBV strain in specific-pathogen-free (SPF) hens were characterized in comparison to Massachusetts (Mass) IBV. In 30-week-old SPF hens, Mass or CA1737/04 IBV infections were carried out, while the third group was maintained as a control group. Following infection, we evaluated clinical signs, egg production, viral shedding, serology, necropsy examination, and histopathology during a period of 19 days. Also, certain tissue affinity parameters were investigated, which involve localization of viral antigens and detection of viral RNA copies in designated tissues. Our findings indicate that infection with CA1737/04 or Mass IBV strain could induce significant clinical signs, reduced egg production, and anti-IBV antibodies locally in oviduct wash and systemically in serum. Both IBV strains showed detectable levels of viral RNA copies and induced pathology in respiratory, renal, enteric, and reproductive tissues. However, CA1737/04 IBV strain had higher pathogenicity, higher tissue tropism, and higher replication in kidney, large intestine and different segments of oviduct compared to the Mass IBV strain. Both IBV strains shed viral genome from the cloacal route, however, the Mass IBV infected hens shed higher IBV genome loads via the oropharyngeal route compared to CA1737/04 IBV-infected hens. Overall, the current findings could contribute to a better understanding of CA1737/04 IBV pathogenicity in laying hens.